Revitalization of Ilmu Falak within the Intellectual Tradition of Traditional Pesantren: A Case Study at Dayah Mudi Mesra Samalanga - Kamilan Latif, Ikhsan (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Abstract Islamic astronomy (ilmu falak) holds a strategic position within the corpus of Islamic sciences, supporting the implementation of religious practices such as determining the beginning of the Hijri months. Historically, this field was one of the most prominent branches of knowledge in the Islamic world. However, its role has gradually diminished, particularly in traditional pesantren (Islamic boarding schools), which tend to prioritize Fiqh and other branches of Islamic studies. The lack of experts, limited facilities, and the dichotomy between hisab (astronomical calculations) and rukyat (moon sighting) have further exacerbated this situation, threatening the existence of Islamic astronomy in traditional pesantren, including in Aceh. This study aims to analyze the content of Islamic astronomy taught at Dayah MUDI Mesra Samalanga, Bireun, Aceh, and to explore strategies for its development to reintegrate it as an essential part of the pesantren curriculum. Using an empirical descriptive approach with qualitative methods, this research collected data through observation, in-depth interviews, and document studies. The findings reveal that Islamic astronomy has been reintroduced into the curriculum of Dayah MUDI Mesra as an innovative step toward revitalizing the heritage of Islamic sciences. The strategies designed include enhancing the capacity of educators, providing necessary facilities, and integrating modern scientific approaches into the teaching process. These efforts are expected not only to preserve Islamic astronomy within the dayah environment but also to make it relevant in addressing contemporary challenges.